Why livestock greenhouse gas emissions matter in Africa - International Livestock Research Institute (International Livestock Research Institute, 2019)
At ILRI's Mazingira Centre, a protocol has been developed that has been used to derive the first accurate Tier 2 emission factors for smallholder livestock systems in Africa. The research is informing ways of reducing emissions per kilogram of milk and meat produced by improving the productivity of African livestock.